‘A promise is a promise… but what about threats?’: an English-Spanish contrastive analysis of the verbs promise-prometer and threaten-amenazar - Maíz-Arévalo, Carmen (Kalbotyra, 2017)
The aim of this paper is to investigate ‘I promise’ and its counterpart in (Peninsular) Spanish prometo. After briefly revisiting the theoretical debate on performativity and performative verbs, the paper adopts a corpus-based approach to quantify the main uses of ‘I promise’ in both languages. This contrastive analysis has an ultimate didactic purpose, since these verbs can raise problems of understanding and use for Spanish learners of English as a foreign language (EFL henceforth) and of translation studies. In order to carry out this analysis, the British National Corpus and the Corpus de Referencia del Español Actual were used, manually fine-graining the initial automatic search. To make both datasets comparable, only the oral and the fiction sections were considered since they are both shared by the two corpora. Interestingly, during the analysis there has also emerged an unexpected result which seems to be pointing out to the beginning of a linguistic change in Spanish. Thus, it can be observed that there is an emergent use in Spanish of the verb amenazar (‘to threaten’), sometimes with the action function of “promising”. This emergent use seems to be especially frequent in computer-mediated communication (e.g. blogs, forums, etc.) but it is still extremely rare in English.